2017
DOI: 10.1093/brain/awx295
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous SSBP1 start loss mutation co-segregates with hearing loss and the m.1555A>G mtDNA variant in a large multigenerational family

Abstract: The m.1555A>G mitochondrial DNA variant causes maternally inherited deafness, but shows highly variable clinical penetrance. Using exome sequencing, Kullar et al. identify a hypomorphic mutation in SSBP1 that segregates with hearing loss in a family transmitting m.1555A>G, and serves as a trans-acting genetic modifier of clinical penetrance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…It may be that the role of SSBP1 is more cell-type specific. 45 The variants reported herein are missense changes that affect amino acid residues in close proximity in the SSBP1 tertiary structure. 43 It is likely that biallelic loss of gene function (knockout) would be incompatible with life (http://www.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It may be that the role of SSBP1 is more cell-type specific. 45 The variants reported herein are missense changes that affect amino acid residues in close proximity in the SSBP1 tertiary structure. 43 It is likely that biallelic loss of gene function (knockout) would be incompatible with life (http://www.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, recently, it was reported that a heterozygous start loss variant in the SSBP1 cosegregated with sensorineural hearing loss in a large family harboring the variable penetrance m.1555A>G maternally inherited deafness variant. The authors stated that the SSBP1 variant leads to reduced SSBP1 level and perturbation of mtDNA metabolism, but the presence of an SSBP1 start loss mutation alone was not associated with disease unless in conjunction with the m.1555A>G variant …”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the sequence domain affected by the rRNA mutation, relevant for aminoglycoside interaction and resistance and possibly leading to drug bacterial/human cross‐reactivity, with depression of human mtDNA translation [33,73]. Yet, in vitro experiments strongly indicated the modifying role possibly played by the nDNA [74] and in specific pedigrees the co‐segregation and possible functional relevance of nDNA variants has been documented [75,76].…”
Section: Mitochondrial Diseases With Primary Mutations Affecting Mtdnamentioning
confidence: 99%
“…As cellular organelles present in almost all eukaryotic cells, mitochondria are places where ATP is biosynthesized and are essential for various cellular biological processes, including reactive oxygen species (ROS) generation, intracellular Ca 2+ signaling, heme metabolism, intrinsic apoptosis, mitophagy, metabolism and cell cycle progression (Yien et al, 2014;Picard et al, 2016;van der Bliek et al, 2017;Gómez-Durán et al, 2018). Genetic mutations in mitochondrial DNA (mtDNA) and perturbations in mitochondrial proteins can cause dysfunction of mitochondria that has been shown to be tightly associated with many mitochondrial diseases and cancer (Taylor and Turnbull, 2005;Garone et al, 2012aGarone et al, ,b, 2013Gómez-Durán et al, 2012;Ronchi et al, 2012;Kullar et al, 2017;Chinnery and Gómez-Durán, 2018;Garone and Viscomi, 2018;Andreazza et al, 2019). Therefore, mitochondria are promising targets for the treatment of these diseases (Gómez-Durán et al, 2010;Zong et al, 2016;Dong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%